The Fissure Swarm of Tungnafellsjökull: Recent movements - Þórhildur Björnsdóttir 1983- (2012)
Fissure swarms consist of clusters of normal faults, tensile fractures and volcanic fissures, and often extend from a central volcano. Fissure swarms are often referred to as rift zones, can be found in intraplate, island arc and spreading center volcanoes on Earth, as well as on Venus and Mars. The Tungnafellsjökull fissure swarm is located in Central Iceland Volcanic Zone near the center of the hot spot of Iceland and the triple junction between the Eurasian plate, North-American plate and the Hreppar microplate. The volcanic system of Tungnafellsjökull is a relatively inactive system and only two small Holocene fissure lavas can be associated with the system, the Tunguhraun lava and the Dvergar lava. To gain an overview of the fissure swarm of Tungnafellsjökull and to grasp the interaction between the volcanic system, the fissure swarm and the plate boundary, active fractures and fissures that relate to the volcanic system were mapped. The area, which is approximately 1450 km2, was mapped both from aerial photographs and from the ground. The fissure swarm is, at most, about 40 km in length and 20 km wide. The fissure swarm is wider than the Tungnafellsjökull central volcano and passes it rather than extends from it. A ground check revealed evidence of recent movements in the fissure swarm indicating more activity in the swarm than previously thought. Three types of structures were found that indicated recent movements. Type 1 is a step in a glacial ground moraine that normally doesn’t have any obvious features. The step thus indicates movements in the Holocene. Type 2 and 3 are sinkholes or fractures on the ground. Both these types indicate movements in the Holocene but type 3 has open wounds in the rim of the sinkholes and the edge of the fractures that indicates more recent movements. Earthquake data from the area and InSAR images from the Gjálp eruption revealed two or three tectonic events that may have led to these recent movements. The first event occurred in October 1996 during the Gjálp eruption, the ...